(untitled) (Eurasian Scientific Herald, 2022)
The COVID-19 coronavirus pandemic, declared by the World Health Organization (WHO) on 11.03.2020, has stimulated the search for treatment and prevention of this disease in many countries around the world. The rapid phase of the development of the disease is the viral phase, when it is still possible to use antiviral drugs, for example, ivermectin or hydroxychlorakine, and the inflammatory phase, when the virus penetrates into the lower parts of the lungs and enters the circulatory system. This phase of the disease is fraught with complications, sometimes requiring the use of ventilation, and with an unfavorable combination of risk factors - and to death. In the literature devoted to the topic of COVID-19, the term "Post-Covid syndrome" appeared, which describes the defeat of the central and peripheral nervous system, thrombosis of the vessels of various organs, damage to the gastrointestinal tract and skin. We present a rarer complication, however, characteristic of the Republic of Uzbekistan. We will talk about aseptic necrosis of the joints and tubular bones (bone infarction).